A cadaveric study on prevalence, morphology, morphometry, and histology of os peroneum in the South Indian population - Jincy Raj C; Lizamma Alex; Gaddam Vijaya Lakshmi; Nithin K Raju (Asian Journal of Medical Sciences, 2024)
Background: The complex framework of the human foot enables movement and weight support. The os peroneum (OP) is a sesamoid bone located in the tendon of peroneus longus. Though tiny, it plays crucial roles in foot movement and arch stability injuries to the tendon are significant, and the OP itself can fracture, dislocate, or impinge. Its presence, size, and even histological type influence the proper functioning of the foot. Studying this sesamoid bone, with its variable prevalence and morphology, can fill gaps in foot and ankle pathology research. Aims and Objectives: To analyze the prevalence, morphology, morphometry, and histology of OP in human adult cadavers in the South Indian population. Materials and Methods: Forty-two formalin-fixed human adult cadaveric free lower limbs were selected and studied from the Department of Anatomy, Pushpagiri Institute of Medical Sciences and Research Centre, Tiruvalla, Kerala. The prevalence of OP in peroneus longus tendons (PLT) and its various configurations were carefully observed, along with their histological types, and then statistical analysis of the data was done using SPSS version 20. Results: Thirty-nine out of the forty-two free lower limbs showed the presence of an OP bearing a smooth oval facet, except for one OP with a round facet. All OP were invariably present in the tunnel for PLT on the plantar surface of the cuboid bone. Three different histological types of this tissue were observed, i.e., osseous, cartilaginous, and fibrous. Conclusion: The present study has attempted to fill the gap in the research data regarding OP in the adult South Indian population. In addition, the knowledge of OP and its configuration in PLT could provide a better radiological and clinical approach to mid- and fore-foot pathologies.